(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
The eye occupies a central place in the teaching of Jacques Lacan. In particular, it finds its almost final formulation in Seminar X (1962-63) and Seminar XI (1964). In these Seminars the field of vision is no longer the place of illusion and mirage of the subjective identity, but it becomes the same field crossed by Freud’s Unheimlich, namely that of the sudden apparition of what is invisible. ‘Look’ is the name that Lacan gives to this appearance. The effects of what Lacan calls the ‘look function’ are: a radical alteration of the coordinates of the visual field and an effect of anguish. In such a perspective, the visual field becomes the proper place to radicalize the idea of the ‘subversion of the subject’: the subject doesn’t look, he/she is looked, the gaze looks at the subject, grabs him/her, and, in doing so, it determines the subject. Thus, Lacan reduces the subject to a claim, a need, that crosses and distorts the visual field. This distortion forces the subject to meet his/her condition of object. From this point of view, visual arts are a privileged territory to establish a certain relationship with the constant distortion of the eye (since aesthetics is, after all, ethics), therefore with that objectual condition that each subject embodies.